Viral infected cells reveal distinct polarization behavior; a polarimetric microscopy analysis on HSV infected Vero and HeLa cells. (March 2021) - Amiri, Saeed; Abedini, Mitra; Badieyan, Saeedesadat; Vaezjalali, Maryam; Akhavan, Omid; Sasanpour, Pezhman
Highlights: The optical polarization properties of virus-infected cells are studied. Infection with HSV, changes the polarization properties of HeLa and Vero cells. The extracted parameter 'b' discriminates between infected and non-infected cells. Different host cells show non-identical polarization properties while infected. Abstract: The optical polarization properties of virus-infected cells have been measured, analyzed, and compared with the uninfected cells. In this regard, Vero and HeLa cells have been used as the host for Herpes simplex viruses (HSV). By using polarization microscopy imaging technique, the Mueller matrix images of infected and uninfected cells have been recorded. Through image processing and further analysis, the polarization properties of host cells are compared with their infected ones. For quantitative analysis, the multispectral Mueller matrix transformation (MMT) parameters (A and b) are calculated to identify the microstructural differentiations between uninfected and infected cells by HSV. The results of our study show that the structural dependent polarization parameters of A and b are sensitive to the infection situation while, the effect of infection on different cells could be distinguished through these parameters accordingly. The polarimetric microscopy imaging and extracted polarization parameters could be considered as an impressive competitor for time-consuming, expensive, and operator dependent available techniques. Graphical abstract: Image, graphical abstract